Optimizing the Application of Complete Microfertilizer in Fertigation for Cayenne Pepper (Capsicum frutescens L.) - Azzuhdy, Muhammad Zakiyuddin Siroj; Suketi, Ketty; Susila, Anas Dinurrohman; Krisantini , Krisantini (Journal of Tropical Crop Science, 2026)
Cayenne pepper (Capsicum frutescens) is one of the important horticultural commodities in Indonesia. According to Central Statistics Agency data, annual consumption has been rising amid fluctuating production, including a 37.68-thousand-ton decline in 2023 compared with 2022. Cayenne pepper requires a specific nutrient profile to achieve optimal yields. Micronutrients, including boron, copper, iron, manganese, molybdenum, and zinc, are vital for photosynthesis, flower development, and nutrient uptake; deficiencies impair growth, fruit quality, and disease resistance, underscoring the need for balanced fertilization. Micronutrient deficiencies can reduce plant growth, fruit quality, and disease susceptibility. Research on micronutrient provision in cayenne pepper plants remains limited. This research aims to determine the most effective method of nutrient application for cayenne pepper plants. The design used was a single-factor randomized group design. The results of the study demonstrate that micronutrient applications can increase the height and diameter of cayenne pepper stems, with foliar spray applications yielding the best response in terms of vegetative parameters. However, micro-nutrient application has not significantly affected the yield and yield components of cayenne pepper.